Influence of sleep duration and sex on age-related differences in heart rate variability: Findings from program 4 of the HAIE study - Gonzales, Joaquin U; Elavsky, Steriani; Cipryan, Lukáš; Jandačková, Vera; Burda, Michal; Jandačka, Daniel (Sleep medicine, 2023)
Heart rate variability (HRV) is an important marker of cardiac autonomic regulation and health. We examined the influence of sleep duration and sex on HRV in younger and middle-aged adults. Cross-sectional data (888 participants, 44% women) were analyzed from Program 4 of the Healthy Aging in Industrial Environment study (HAIE). Sleep duration was measured across 14 days using Fitbit Charge monitors. Short-term EKG recordings were used to evaluate HRV in the time (RMSSD) and frequency domains (low frequency (LF) and high frequency (HF) power). Regression analysis showed age was associated with lower HRV across all HRV variables (all P < 0.001). Sex was a significant predictor for LF (β = 0.52) and HF (β = 0.54; both P < 0.001) in normalized units. Similarly, sleep duration was only associated with HF in normalized units (β = 0.06, P = 0.04). To explore this finding further, participants within each sex were separated into groups based on age (<40 and ≥ 40y) and adequate sleep duration (<7 and ≥7 h). Middle-aged women with sleep durations <7 h, but not ≥7 h, had lower HRV than younger women after adjusting for medications, respiratory frequency, and cardiorespiratory fitness (peak VO2). Middle-aged women with sleep durations <7 h also had lower RMSSD (33 ± 2 vs. 41±4 ms, P = 0.04), HF power (5.6 ± 0.1 vs. 6.0 ± 0.1 log ms2, P = 0.04), and HF in normalized units (39 ± 1 vs. 48 ± 2, P = 0.01) than middle-aged women with sleep durations ≥7 h. In contrast, middle-aged men irrespective of sleep duration had lower HRV than younger men. These results suggest that adequate sleep duration may positively influence HRV in middle-aged women but not men.
Keywords: délka spánku; Humans; lidé středního věku; VO(2); životní prostředí; Environment; Female; Sleep duration; dospělí; Heart Rate; lidé; HRV; Sleep Duration; Sleep; Adult; Heart rate variability; ženské pohlaví; Male; srdeční frekvence; Middle Aged; zdravé stárnutí; Healthy Aging; Cross-Sectional Studies; Fitbit; Aerobic fitness; mužské pohlaví; aging; průřezové studie